Bortezomib moduliert die Glukokortikoidresistenz in B-Vorläufer-Zelllinien der akuten lymphoblastischen Leukämie - Junk, S.; Cario, G.; Wittner, N.; Stanulla, M.; Scherer, R.; Schlegelberger, B.; Schrappe, M.; von Neuhoff, N.; Lauten, M. (Klinische Pädiatrie, 2015)
Background: The response to initial glucocorticoid (gc) treatment is a reliable stratification factor in childhood acute lymphoblastic leukemia (ALL) and may predict the response to multi-agent chemotherapy. In a former study we detected that the valosin-containing protein (VCP, cdc48), a member of the ubiquitin proteasome degradation system (UPS), is altered in gc-resistant leukemic cells suggesting that the associated pathways might be involved in chemotherapy resistance in childhood ALL.Methods: Human B-cell precursor leukemia cell lines, gc-resistant MHH-cALL-2 and gc-sensitive MHH-cALL-3, were treated with prednisolone and various concentrations of bortezomib. Viability and apoptosis rates were determined.Results: Both cell lines showed a dose-dependent increase in caspase activity after bortezomib single treatment. The gc-sensitive cells showed an additive effect after combined treatment with prednisolone and bortezomib. In contrast, both cell lines showed a reduced viability and enhanced propidium iodide positivity after combined treatment as determined by flow cytometry. Western blot analyses of poly-(ADP-ribose) polymerase 1 (PARP-1) suggested that combined treatment promote necrotic cleavage of PARP-1 in gc-resistant cells. Furthermore, after prednisolone treatment the UPS associated proteins VCP and NFκB-inhibitor IκBα were differentially modulated in gc-resistant cells.Conclusions: The proteasome inhibitor bortezomib seems to sensitize gc-resistant childhood ALL cells for prednisolone-induced cell death.
Keywords: acute lymphoblastic leukemia; drug resistance; apoptosis; necroptosis; prednisolone; bortezomib